The Administration of Heat Shock Protein-70 Bacterial Homolog (Dnak) Improves the Cumulative Survival and the Expression of Immune-Related Genes in Gnotobiotic Full-Sibling Sea Bass Larvae Challenged with Vibrio Anguillarum - Goldstein-Vasquez, M; Reyes-Lopez, F; Vallejos-Vidal, E; Santillan-Araneda, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Heat shock proteins (HSPs), particularly HSP70, play a vital role in fish immune defense against pathogens. The administration of DnaK (bacterial homolog of HSP70) may be a strategy to potentiate the immune response and survival of aquatic organisms. This study evaluates the effect of cells overexpressing DnaK on mortality and immune-related gene expression in gnotobiotic sea bass larvae challenged with Vibrio anguillarum. Larvae were subjected to different treatments: NB (no bacteria), YS0 (E. coli with no plasmid), YS1 (E. coli expressing truncated DnaK), and YS2 (E. coli expressing DnaK), and then infected with V. anguillarum at 7 days post-hatching (dph). Mortality was monitored, and RT-qPCR was used to evaluate immune gene expression at 0, 18, 24, 36, and 120 hpc. While no significant variations were recorded in the non-challenged larvae, constant and sustained mortality was observed in challenged larvae from 60 to 120 hpc. However, lower mortality was observed in the larvae treated with DnaK. DnaK treatment promoted the expression of antimicrobial (hepcidin, transferrin) and chemotaxis genes (ccl4), which was further enhanced after a challenge with V. anguillarum, in conjunction with the modulation of il1β and il-8 at 120 hpc. These findings suggest that DnaK induces a potent innate immune response, improving survival against V. anguillarum and supporting its potential use as a disease-preventive strategy in aquaculture. © 2025 by the authors.